Neutrophil-lymphocyte ratio and D-dimer to predict outcomes of length of hospitalization and mortality of COVID-19 in children - Suryadi Nicolaas Napoleon Tatura; Susan Nathalia Budihardjo; Johny Lambert Rompis; David Soelingan Waworuntu; Vivekenanda Pateda (Paediatrica Indonesiana, 2025)
Background Biomarkers such as the neutrophil-to-lymphocyte ratio (NLR) and D-dimer have proven predictive of mortality in adults with COVID-19, but their utility in pediatric patients remains underexplored. Objective To evaluate for associations between NLR and D-dimer with hospital length of hospitalization and mortality in children. Methods This retrospective cross-sectional study analyzed pediatric COVID-19 cases at Prof. Dr. R.D. Kandou Hospital, Manado (January 2021–September 2022). Children aged 1 month to 18 years with confirmed SARS-CoV-2 by RT-PCR were included. Children with incomplete data or immuno-compromised status were excluded. Data on demographics and laboratory parameters were analyzed using descriptive statistics, correlation, and linear regression Results This study included 65 pediatric COVID-19 patients, with a median age of 60 months and a balanced gender distribution. The median NLR was 1.3 (IQR 0.8–2.4), and the median D-dimer was 1.1 (IQR 0.4–11.0) mg/L. Three patients (5%) died, and the median length of hospitalization was 10 (IQR 7–16) days. No significant correlation was found between NLR and D-dimer (r=0.07; P=0.576). Similarly, NLR was not associated with length of hospital hospitalization (r=0.20; P=0.120) or with mortality (P=0.482). D-dimer levels, in contrast, demonstrated a strong positive association with length of hospitalization (r=0.59; P<0.001) but were not significantly correlated with mortality (P=0.316). Although not statistically significant, D-dimer levels tended to be higher in non-survivors compared to survivors. In regression analysis, higher D-dimer levels were independently associated with longer hospitalization duration (β=0.49; 95% CI 0.29 to 0.70; P<0.001) after adjusting for NLR, age, and platelet count. However, NLR showed no significant relationship with either hospitalization duration or mortality. Conclusion Pediatric COVID-19 patients showed normal NLR and elevated D-dimer levels. Elevated D-dimer is associated with prolonged hospitalization, but not with mortality.